A new species of Fissidens (Fissidentaceae, Bryophyta) from Peninsular Malaysia - Nur Syazwana; Gaik Ee Lee; Nik Norhazrina (Malaysian Nature Society, 2025)
A new species of moss, Fissidens Damanhurii Norhazrina & Syazwana from Gunung Senyum Recreational Park, Pahang, Peninsular Malaysia is described and illustrated. The species is characterized by large cells, short costae, leaves with differentiated margins of small, isodiametric cells and weakly limbate vaginant laminae on the perichaetial and subperichaetial leaves. The new species belongs to the subgenus Aloma and a key to the species of Fissidens subgenus Aloma is provided